Kierkegaard om tiden og det timelige - Wegener, Mogens (Religionsvidenskabeligt Tidsskrift, 1987)
This paper offers a discussion of the notions of time and temporality in Kierkegaard based on two of his major works, “Philosophical Fragments” and “The Concept of Dread”. After a general introduction to the status of the two notions within the pseudonymous authorship as a whole, two interesting theses are made the object of further inquiry: (1) the thesis of the mind-dependency of temporality proper and (2) the thesis of the revocability of the past as a precondition of the possibility of repentance. As regards the first thesis it is argued that it should be understood within the context of the distinction between natural time which is infinite succession and human temporality which is characterized by the triad of past, present & future: whereas natural time is objective, human temporality is subjective. But to Kierkegaard, subjectivity is truth; and the ultimate aim & goal of spirit (which is a synthesis of body & soul) is to transcend nature in the unique moment of decision = devotion (that moment which is in itself a synthesis of temporality & eternity). Therefore, from the point of view of the existing thinker, it is subjective time which is real whereas objective time is an illusion. As regards the second thesis it is argued that although Kierkegaard opposes the Hegelian view that the contingent becomes necessary by its receding into the past, he does not thereby deny that the past is, in a certain sense, unchangeable (for if it was not, either there would be nothing to repent, or the subjective truth of repenting & forgiving might also be an illusion; but that is truly absurd). In fact, my main point is that although Kierkegaard denies the possibility of imposing motion onto logic, his very own reflections concerning the dialectics of being and existence make an important contribution to a new logic of time and motion in time.